Audit Tata Kelola Teknologi Informasi Program Studi Sistem Informasi Sekolah Tinggi Manajemen Informatika Dan Komputer (STMIK) Lombok Menggunakan - Ahmad Susan Pardiansyah - STMIK Lombok (Indonesian Journal on Software Engineering (IJSE), 2015)
Abstract - This audit of information technology governance aimed at mapping the level of Information Technology maturity process implemented in Information System Study Program in the School of Information Management and Computer (STMIK) Lombok in order to measure  the position process. This audit used Cobit Framework to formulate relevant IT Governance recommendations for the study program in order to attain the expected Maturity Level based on the formulated IT Governance recommendations for the System Information Study Program. Based on the Maturity Level, the result showed that the score reached the average score 2, which is Repeatable, meaning that the Information Technology Study Program has  pattern in governing the process based on repeated experience which had been conducted previously. Information System Study Program has applied procedures that were followed by the staffs, but there were no trainings and formal communications according to the standard procedures for the staffs therefore full responsibility and trust were given to each of the individuals which may have led to misconduct. Meanwhile, the result of Maturity Level identification shows that 16 domains were on Repeatable Level, 2 domains were on Initial/Ad Hoc level, and 2 domains were on Defined Level. Based on the mapping utilising Business Golas of the School of Information Management and Computer (STMIK) Lombok and COBIT 4.1, it was shown that there were 9 Business Goals, 8 Information Technology (IT) Goals, 31 Information Technology (IT) Process of each Business Goals, and 125 Control Objectives which were needed to be considered.   Key Word: cobit 4.1, Maturity level, Business goals, IT Goals, IT Process, Control Objectives   Abstrak – Audit tata kelola teknologi informasi ini bertujuan untuk memetakan tingkat maturity proses TI pada Program Studi Sistem Informasi Sekolah Tinggi Manajemen Informatika dan Komputer (STMIK) Lombok sehingga dapat diukur posisi proses. Audit ini menggunakan Framework Cobit untuk merumuskan rekomendasi IT Governance apa saja yang bisa diberikan kepada Program Studi, sehingga dapat tercapai Maturity Level yang diharapkan berdasarkan rumusan rekomendasi IT Governance pada Program Studi Sistem Informasi. Berdasarkan Level Kematangan (Maturity Level) didapatkan level yang dicapai rata-rata memiliki nilai 2 yaitu Repeatable yang artinya adalah Prodi SI memiliki pola untuk mengelola proses berdasarkan pengalaman yang berulang-ulang yang pernah dilakukan sebelumnya. Prodi SI telah menerapkan prosedur untuk dipatuhi oleh karyawan, namun belum ada pelatihan dan komunikasi formal dari prosedur standar kepada setiap karyawan sehingga tanggung jawab dan kepercayaan penuh diberikan kepada individu yang memungkinkan terjadinya penyimpangan. Sedangkan Hasil identifikasi Maturity Level penulis mendapatkan 16 domain berada pada Level Repeatable, 2 domain pada level Initial/Ad Hoc, dan 2 domain pada level Defined. Berdasarkan hasil mapping penulis antara business goals Sekolah Tinggi Manajemen Informatika dan Komputer (STMIK) Lombok dan COBIT 4.1, terdapat 9 Business Goals, 8 Information Technology (IT) Goals, 31 Information Technology (IT) Process dari masing-masing Business Goals, dan 125 Control Objectives yang harus diperhatikan. Kata Kunci: cobit 4.1, Maturity level, Business goals, IT Goals, IT Process, Control Objectives